2013
DOI: 10.1097/ccm.0b013e31826a4082
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Critically Ill Patients in ICUs in Mainland China*

Abstract: Critically ill patients in ICUs in Mainland China exhibited a case mix similar to those of Western countries, although there are significant differences in intensive care unit admission rates and disease severity between Western and Chinese ICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 31 publications
7
47
2
2
Order By: Relevance
“…This observation is in line with reports from other studies [5]- [7]. The mean age of the total population was 58.92+13.89 years covering a age ranges from 14 to 102 years while results from different studies revealed lower mean age [5], [8] as well as higher mean age [6], [8], [9]. Table 1 shows that almost fifty three percent of the total population were aged between 40-60 years, 49.61% aged 60years and above and 13.44% between the age group of 20-40 years.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This observation is in line with reports from other studies [5]- [7]. The mean age of the total population was 58.92+13.89 years covering a age ranges from 14 to 102 years while results from different studies revealed lower mean age [5], [8] as well as higher mean age [6], [8], [9]. Table 1 shows that almost fifty three percent of the total population were aged between 40-60 years, 49.61% aged 60years and above and 13.44% between the age group of 20-40 years.…”
Section: Resultssupporting
confidence: 83%
“…Sixty three percent were male while 37 % were female being a ratio of male to female 1:06. This observation is in line with reports from other studies [5]- [7]. The mean age of the total population was 58.92+13.89 years covering a age ranges from 14 to 102 years while results from different studies revealed lower mean age [5], [8] as well as higher mean age [6], [8], [9].…”
Section: Resultssupporting
confidence: 81%
“…Life Support Withholding and Withdrawing policies were not considered, as well as the discharge to Intermediate Care Units, which may have affected both the percentage of patients who died and the length of stay in the ICU. 35 Although mean APACHE II scores were annually assessed, we assumed that other factors that may influence upon mortality in critically ill patients, 36 such as the number of patients with malignancies or septic complications (septic shock or adult respiratory distress syndrome) did not vary during the study period, although this aspect was not examined. It is also assumed that during the 6-year study period, important changes in the overall care of critically ill patients did not occur, although mortality in some particular groups of patients may have decreased as a consequence of changes in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Severe sepsis can cause multiple organ failure, which has a high mortality [1]. Etomidate is commonly used as an intravenous anaesthetic drug in clinical practice.…”
Section: Introductionmentioning
confidence: 99%